PENDAMPINGAN USAHA EKONOMI KREATIF PADA DESA WISATA PUJON KIDUL - Fauzik Lendriyono; Titiek Ambarwati; Iqbal Ramadhani Fuadiputra (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Malang, 2021)
This community service program tries to answer problems related to economic development that must be carried out by the Pujon Kidul tourist village, based on information that there are facilities and tourist attractions that are developing are not supported by other economies. This area also does not have any characteristics related to its superior products. Some of the resources that can be utilized are the abundant bamboo land which can be used as various processed products that have economic value. This development is not only for processing bamboo, but how bamboo can be packaged properly which will be in great demand by tourists visiting the Pujon Kidul area. Some of the programs that will be carried out are training in bamboo material processing, making bamboo packaging, and marketing the finished bamboo products to attract them. With the creative economy development program, we, the community service team, hope that the creative economy of the community will eventually have income outside the existing ones. Through merchandise in the form of processed bamboo taken from the potential of the surrounding area. The hope is that residents will have income not only from existing tourist attractions. Because seeing the tourist areas that are visited by many tourists, apart from some handicraft products produced by the service team, they also provide material related to the use of bamboo and must also be used at several points in tourist attractions in order to image the Pujon Kidul tourist area that is superior to its bamboo products.Based on the results of the training that has been carried out by the service team, it can be said that the processed bamboo produced has more selling value and can eventually be sold in bulk. Through this service program, several bamboo products can be produced, ranging from glass to fountains made from bamboo. These products will later become characteristic of Pujon Kidul village as merchandise that can be brought home and can be used in several units in the village.